Identification of Hazardous Road Locations on Dhaka-Khulna National Highway - Paul, Amit Kumar; Adhikary, Roni; Shaik, Md Ebrahim; Banarjee, Supriya; Ashifin, Jannatul; Hasib, Qazi (Journal of Engineering Science, 2025)
Road crashes are a major concern in the transportation sector of developing countries like Bangladesh. According to “Bangladesh Passengers Welfare Association” (BPWA) about 6,642 deaths and 21,755 injuries and more accidents occurred in 2022 in Bangladesh. This research analyzes the various accident data from the year 2018 to 2022 in route N8 (Dhaka – Mawa – Faridpur – Gopalganj – Bagerhat National Highway) in Bangladesh. This study identifies accident-prone locations, often referred to as Hazardous Road Locations (HRL) on Dhaka-Khulna (N8) Highway. The relevant Accident Report Forms (ARF) were collected from the Officer in Charge (OC) of the Highway Police Station (Bhatiapara Highway Police Station and Bhanga Highway Police Station). The Accident Frequency Analysis approach was used to identify accident-prone sites, which were then mapped using a Geographic Information System (GIS) on the Dhaka-Khulna National Highway. Sreenagar Filling Station Road, Bogail Bus Stop, Bhanga Gol Chottor, and 19 more locations were identified as HRL on route N8. Head-on collisions, rear-end collisions, and pedestrian hits are the most dominant types of accidents on route N8. The result from this study shows that the maximum number of accidents occurred in Daylight. The result clearly indicates that buses were the most common type of vehicle involved in accidents on Route N8. Journal of Engineering Science 15(2), 2024, 121-130